2018
DOI: 10.1029/2018ja025196
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Observations of a Dispersive Flapping Event of Magnetotail Current Sheet

Abstract: A kink‐like flapping event of Earth magnetotail current sheet, which consists of two frequency bands successively, is studied by the multipoint observations of Cluster. The multipoint analysis of Cluster observations demonstrates that the higher frequency band (period is about 10 min) has faster propagation velocity (about 30 km/s), shorter wavelength (about 3 RE), and smaller amplitude (1–1.5 RE). In contrast, the lower frequency band (period is about 22 min) shows slower propagation velocity (about 21 km/s),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(60 reference statements)
4
16
0
Order By: Relevance
“…On the other hand, the asymmetry of the kink‐like flapping shown by Figures a and d indicates that the kink‐like flapping wave is dispersive; that is, the kink‐like flapping wave with shorter period has faster propagation velocity at the duskside. The dispersive properties are consistent with the recent study of Rong et al () where they reported the kink‐like flapping waves with shorter period and faster propagation velocity when the background undisturbed CS is thinner. Evidently, relative to the dawnside, the background tail CS is thinner at duskside; thus, the dispersive properties demonstrated by Figures a and d are reasonable.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the asymmetry of the kink‐like flapping shown by Figures a and d indicates that the kink‐like flapping wave is dispersive; that is, the kink‐like flapping wave with shorter period has faster propagation velocity at the duskside. The dispersive properties are consistent with the recent study of Rong et al () where they reported the kink‐like flapping waves with shorter period and faster propagation velocity when the background undisturbed CS is thinner. Evidently, relative to the dawnside, the background tail CS is thinner at duskside; thus, the dispersive properties demonstrated by Figures a and d are reasonable.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In past decades, numerous studies noticed that the Earth's magnetotail current sheet (CS) often flaps up and down, which accounts for multiple crossings of the local CS by spacecraft (e.g., Lui et al, 1978;Sergeev et al, 1998;Speiser & Ness, 1967;Toichi & Miyazaki, 1976). Using the four-point analysis of the Cluster (Escoubet et al, 2001), many studies demonstrated that the flapping CS can propagate as kink-like waves from the midnight region toward both magnetotail flanks, with a velocity of several tens of km/s (Petrukovich et al, 2006;Rong et al, 2018;Runov et al, 2005;Sergeev et al, 2003Sergeev et al, , 2004Shen et al, 2008;Sun et al, 2014;Zhang et al, 2002Zhang et al, , 2005. CS flapping motions are observed not only in the Earth's magnetotail but also in the magnetotails of other planets, such as Mercury (Poh et al, 2017), Venus (Rong, Barabash, Stenberg, Futaana, Zhang, Wan, Wei, Wang, Chai, et al, 2015), Mars (DiBraccio et al, 2017), Saturn, and Jupiter (Volwerk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated results demonstrate that the spatial amplitude during this period is about 1–2 R E , which is consistent with the typical amplitude reported in previous studies (e.g. Petrukovich et al., 2006; Rong et al., 2018a; Sergeev et al., 2003, 2004).…”
Section: Application and Testsupporting
confidence: 92%
“…Flapping motions with a typical period of several minutes are large‐scale movements of the current sheet in the north‐south direction, manifesting as variations of the X GSM component of the magnetic field with an amplitude up to 10s nT (Rong et al., 2010; Volwerk et al., 2013; Wu et al., 2016). The flapping on the duskside propagates duskward, whereas the flapping on the dawnside propagates dawnward, indicating that it originates in the central part of the magnetotail (Gao et al., 2018; Rong et al., 2018; Sergeev et al., 2004). They can be generated by magnetic double gradient instabilities (Duan et al., 2018; Erkaev et al., 2008; Korovinskiy et al., 2013), magnetic reconnections (Wei et al., 2019) as well as variations of the solar wind parameters (Juusola et al., 2018; Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%